2005
DOI: 10.1107/s1600536805006173
|View full text |Cite
|
Sign up to set email alerts
|

Di-μ-chloro-bis{chloro[3,5-dimethyl-1-(thiocarbamoyl)pyrazole-κ2N2,S]cadmium(II)}

Abstract: Di-l-chloro-bis{chloro[3,5-dimethyl-1-(thiocarbamoyl)pyrazole-j 2 N 2 ,S]cadmium(II)}

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Therefore, the lack of an additional phenyl ring and of the thiazole ring results in two important consequences: (i) the sulfur atom participates in the coordination of the metal ion, (ii) the lack of the thiazole ring allows for bigger conformational flexibility, as presented by a bigger value of the dihedral angle created between the N1 pyrazole and chelate rings. This is confirmed by the results obtained by Radosavljevic ´et al 34 for Cd 2 L 00 2 Cl 4 (L 00 = 3,5-dimethyl-1H-pyrazole-1-carbothioamide). They showed that the pyrazole and chelate rings remain coplanar with an angle of 19.8( 5 26 The mutual conformation of L 0 or L 00 ligands in complexes described by the 1 : 2 metal : pyrazole ligand stoichiometric ratio usually ranges from 50-601 in the reported structures.…”
Section: Molecular Structures Of 1a 6a 8a and 5bsupporting
confidence: 86%
“…Therefore, the lack of an additional phenyl ring and of the thiazole ring results in two important consequences: (i) the sulfur atom participates in the coordination of the metal ion, (ii) the lack of the thiazole ring allows for bigger conformational flexibility, as presented by a bigger value of the dihedral angle created between the N1 pyrazole and chelate rings. This is confirmed by the results obtained by Radosavljevic ´et al 34 for Cd 2 L 00 2 Cl 4 (L 00 = 3,5-dimethyl-1H-pyrazole-1-carbothioamide). They showed that the pyrazole and chelate rings remain coplanar with an angle of 19.8( 5 26 The mutual conformation of L 0 or L 00 ligands in complexes described by the 1 : 2 metal : pyrazole ligand stoichiometric ratio usually ranges from 50-601 in the reported structures.…”
Section: Molecular Structures Of 1a 6a 8a and 5bsupporting
confidence: 86%